Increased epicardial adipose tissue thickness is associated with microalbuminuria in hypertensive patients with left ventricular hypertrophy. (2nd January 2021) - Eren, Hayati; Omar, Muhammed Bahadır; Kaya, Ülker; Öcal, Lütfi; İnanir, Mehmet; GÖzek Öcal, Aslı; GenÇ, Ömer; GenÇ, Selin; GÜner, Ahmet; Yetİm, Mucahit
ABSTRACT: Objective: Epicardial adipose tissue (EAT) is a cardiometabolic risk factor, and its possible relationship with hypertension has been previously reported. Microalbuminuria (MA) is associated with target-organ damage, especially in patients with hypertension with left ventricular hypertrophy (LVH) and suggest endothelial dysfunction. This study aimed to investigate the relationship between echocardiographic EAT thickness and presence of MA in patients with hypertension. Methods: A total of 297 newly diagnosed hypertension patients who applied to the outpatient clinic were enrolled consecutively in this study. Patients were divided into two groups regarding the presence of LVH in echocardiography. An age and gender matched control group was set including 156 healthy patients without HT. All subjects underwent transthoracic echocardiography for the measurement of EAT thickness. Spot urine samples were collected for the assessment of MA. Results: In hypertensive patients with LVH, the EAT thicknesses (6.6 ± 1.8 vs 5.3 ± 1.5 vs 5.1 ± 1.3,   p  < .001; respectively) and prevalence of MA (41.2 vs 20.1 vs 3.2%;  p  < .001 respectively) were significantly higher than the other two groups. In hypertensive patiens without LVH, no relationship was found between the presence of MA and EAT thickness. In multivariate regression analyses, EAT thickness (OR: 3.141, 95%CI: 2.425–6.123, p < .001) and left ventricular mass index (OR: 1.339, 95%CI: 1.145–2.143, p = .003) were determined as independent predictors for MA development in hypertensive patients with LVH. Conclusion: Measurement of EAT thickness may help to identify high-risk hypertensive patients for target-organ damage especially among patients with LVH.